A Literature Review on Students' Views on the Utilization of Zoom for English Language Instruction During the Pandemic - Ahmed, Abdulaziz Ahmed Mohammed (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
This research aims to investigate the implementation and effectiveness of using the Zoom application for English Language Teaching (ELT) during the pandemic. The study focuses on students who utilized the Zoom application as a method for ELT. The research methodology combines both quantitative and qualitative approaches, utilizing an online questionnaire to collect data. The researcher analyzed the data, integrated their ideas, and formulated concluding remarks based on the collected information. The review includes three primary studies published between 2020 and 2021. The first study, conducted by Irwandi (2020), examines the implementation of the electric method for ELT through distance learning during the COVID-19 pandemic. The second study, also conducted by Irwandi (2020), investigates students' perceptions of using Zoom and WhatsApp for ELT during the pandemic. The third study, conducted by Suadi (2021), explores the effectiveness of learning-based applications, including Zoom, for ELT in the pandemic era. The review findings indicate that students were able to actively practice English, responded positively to the use of Zoom, and demonstrated the ability to learn independently.